Memaknai Peran Alkitab Dalam Pertumbuhan Rohani Mahasiswa Kristen Melalui Pemuridan Kontekstual Di Surakarta - Efi Nurwindayani (Diegesis : Jurnal Teologi, 2020)
The focus of this research is "Interpreting the Role of the Bible in the Spiritual Growth of Christian Students through Contextual Discipleship in Surakarta." This study aims to find the meaning of the role of the Bible in the spiritual growth of Christian students through Contextual Discipleship in Surakarta. This study used a qualitative research design with a phenomenological approach to the Interpretative Phenomenological Analysis model. Through this research, the writer found the meaning of the Bible's very important role in the spiritual growth of students. Students are aware of many challenges that keep them from growing spiritually. But with the awareness that the Bible is the revelation of God without error and without defects, it is what encourages students to strive to be faithful in studying it so that spiritual growth is continually renewed into mature, Christ-like individuals.